Ultra-high extinction-ratio light modulation by electrically tunable metasurface using dual epsilon-near-zero resonances - Arash Nemati; Qian Wang; Norman Soo Seng Ang; Weide Wang; Minghui Hong; Jinghua Teng (Opto-Electronic Advances, 2021)
The lossy nature of indium tin oxide (ITO) at epsilon-near-zero (ENZ) wavelength is used to design an electrically tunable metasurface absorber. The metasurface unit cell is constructed of a circular resonator comprising two ITO discs and a high dielectric constant perovskite barium strontium titanate (BST) film. The ENZ wavelength in the accumulation and depletion layers of ITO discs is controlled by applying a single bias voltage. The coupling of magnetic dipole resonance with the ENZ wavelength inside the accumulation layer of ITO film causes total absorption of reflected light. The reflection amplitude can achieve ~84 dB or ~99.99% modulation depth in the operation wavelength of 820 nm at a bias voltage of −2.5 V. Moreover, the metasurface is insensitive to the polarization of the incident light due to the circular design of resonators and the symmetrical design of bias connections.